Bidirectional reconfiguration and thermal tuning of microcantilever metamaterial device operating from 77 K to 400 K - Pitchappa, Prakash (2018)
We experimentally report the bidirectional reconfiguration of an out-of-plane deformable microcantilever based metamaterial for advanced and dynamic manipulation of terahertz waves. The microcantilever is made of a bimaterial stack with a large difference in the coefficient of thermal expansion of the constituent materials. This allows for the continuous deformation of microcantilevers in upward or downward direction in response to positive or negative temperature gradient, respectively. The fundamental resonance frequency of the fabricated microcantilever metamaterial is measured at 0.4 THz at room temperature of 293 K. With decreasing temperature, the resonance frequency continuously blue shifts by 30 GHz at 77 K. On the other hand, with increasing temperature, the resonance frequency gradually red shifts by 80 GHz and saturates at 0.32 THz for 400 K. Furthermore, as the temperature is increased above room temperature, which results in the downward actuation of the microcantilever, a significant resonance line-narrowing with an enhanced quality factor is observed due to tight field confinement in the metamaterial structure. The thermal control of the microcantilever possesses numerous inherent advantages such as enhanced tunable range (∼37.5% in this work compared to previously reported microcantilever metamaterials), continuous tunability, and repeatable operations. The microcantilever metamaterial also shows high robustness to operate at cryogenic conditions and hence opens up the possibility of using meta-devices in harsh environments such as space, polar, and deep sea applications.